2008
DOI: 10.1161/strokeaha.107.508655
|View full text |Cite
|
Sign up to set email alerts
|

Transient Global Amnesia

Abstract: Background and Purpose-A hypoxic-ischemic origin of transient global amnesia (TGA) has been suggested on the basis of the observation of infarctlike diffusion-weighted imaging (DWI) abnormalities in some affected individuals. We tested this hypothesis by comparing vascular risk factors, magnetic resonance imaging (MRI) markers of cerebral small-vessel disease, and other evidence of a cerebrovascular disorder between TGA patients with (DWIϩ) and without (DWIϪ) DWI lesions and normal community-based controls. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(40 citation statements)
references
References 41 publications
0
37
2
1
Order By: Relevance
“…Несмотря на это, M. Kushner и W. Hauser [7] не подтвердили эти выводы. В исследованиях с исполь-зованием диффузионно-взвешенной магнитно-резо-нансной томографии (ДВ-МРТ) были обнаружены незначительные, остро возникшие изменения в меди-альных областях височных долей у небольшого числа пациентов с клиническим диагнозом ТГА [8]. Другие авторы предположили наличие связи ТГА с эпилепсией [9,10] и опухолями головного мозга [11,12].…”
Section: Disclosuresunclassified
See 1 more Smart Citation
“…Несмотря на это, M. Kushner и W. Hauser [7] не подтвердили эти выводы. В исследованиях с исполь-зованием диффузионно-взвешенной магнитно-резо-нансной томографии (ДВ-МРТ) были обнаружены незначительные, остро возникшие изменения в меди-альных областях височных долей у небольшого числа пациентов с клиническим диагнозом ТГА [8]. Другие авторы предположили наличие связи ТГА с эпилепсией [9,10] и опухолями головного мозга [11,12].…”
Section: Disclosuresunclassified
“…Studies with diffusion-weighted magnetic resonance imaging (MRI) have found small, acute changes in the mesial temporal areas in a minority of patients with a clinical diagnosis of TGA. 8 Other authors have suggested an epileptic etiology 9,10 and association with brain tumors. 11,12 In recent years, the theory of brain venous congestion has been proposed.…”
mentioning
confidence: 98%
“…However, previous studies reported relatively lower incidence of multiplicity, ranging from 5% to 38%. 7,10,22,23 This may be due to increased detectability of high-resolution DWI for smaller lesions, which were missed on lower resolution by partial volume averaging effects. 7,9,22 Therefore, we think that high-resolution DWI with less partial volume averaging might improve lesion contrast in our study.…”
Section: Discussionmentioning
confidence: 99%
“…10 In line with this theory, magnetic resonance imaging (MRI) studies reported a variable percentage of hippocampal abnormalities displaying restricted diffusion in patients with TGA who lacked vascular risk factors, large-artery stenoses or small-vessel disease, and underlying sources of cardioembolism. 11 In addition, 30-day follow-up MRIs did not show any pathologic findings indicative of previous arterial ischemia. 12 Although these results were fairly consistent, studies evaluating IJV competence and MRI findings in the same patients are not available.…”
mentioning
confidence: 86%
“…In the population investigated by Cejas et al, IJV valve incompetence was observed more frequently on the right side, whereas MRI abnormalities were more often detected in the left mesiotemporal region. [11][12][13] Indeed, MRI diffusion restriction is not a specific finding, as it is also observed in ischemic depolarization and cortical spreading depression. Can venous ischemia and cortical spreading depression represent 2 notmutually exclusive mechanisms?…”
mentioning
confidence: 99%